THE IMPLEMENTATION OF ANTHROPOCENTRISM PARADIGM IN ISLAMIC THEOLOGY STUDIES - Winarto Winarto; Layyinatus Shifa (IAIN Tulungagung, 2022)
Islamic theology is an important classical Islamic studies from the early Islam until now. With the development of science, Islamic theology demanded to always discussed for solving the problem of human life. This research aims to know the development of islamic theology, paradigm of anthropocentrism and it's implementation. This research is a kind of library research with qualitative method. The data will be collected and analyzed using theology and philosophy approach. The most of earlier research criticize the Islamic theology wich usually theocentrically, and not entrying yet the level of anthropologist. So that the research of Islamic theology using the paradigm of anthropocentrism is an important thing. This research concludes that the implementation of the paradigm of anthropocentrism in islamic theology studies can be realized with focusing Islamic theology studies on social humanity problems. Tauhid as manifest of unity and diversity as a based of shaping personality dan the source of morality dan law obedience.